Batch versus Flow Acetalization of Benzaldehyde with HKUST‐1: Diffusion Pathways and Performance Comparison. Issue 7 (1st March 2016) - Piscopo, Calogero G.; Schwarzer, Maud; Herrmann, Michael; Affini, Anna; Pelagatti, Paolo; Maestri, Giovanni; Maggi, Raimondo; Loebbecke, Stefan
Abstract: Understanding the poisoning and deactivation pathways of metal–organic frameworks (MOFs) is an essential goal to boost their application as robust and efficient catalysts in chemical transformations relevant to industrial processes. Herein, the acetalization reaction of benzaldehyde with methanol was investigated by using [Cu3 (BTC)2 ] (BTC=1, 3, 5‐benzenetricarboxylate) as a catalyst. The reaction was performed under batch and continuous flow conditions, and the conversion of benzaldehyde into 1, 1‐dimethoxytoluene proceeded efficiently in the presence of a modest amount of water. Nevertheless, a drastic reduction in the catalytic activity was observed after recycling the MOF for repetitive batch experiments and after prolonged continuous flow tests. Pore clogging of the MOF and partial crystal‐structure modifications, gathered from XRD and pore analyses, suggested grinding the catalyst prior to application; the ground catalyst showed a considerable enhancement in catalytic performance. Abstract : Grind to the flow : The acetalization reaction of benzaldehyde with methanol is investigated by using [Cu3 (BTC)2 ] (BTC=1, 3, 5‐benzenetricarboxylate, also known as HKUST‐1), a copper‐containing metal–organic framework, as the catalyst. The flow mode, in addition to enhancing the productivity and stability of the catalyst, is a powerful tool that can be used to gain useful information on catalyst modifications.